2004
DOI: 10.2337/diacare.27.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Insulin Sensitivity and β-Cell Function in Premenopausal or Early Perimenopausal Women Without Diabetes

Abstract: OBJECTIVE -To assess differences in insulin sensitivity and ␤-cell function between nondiabetic premenopausal or early perimenopausal non-Hispanic white women and African American, Chinese American, Japanese American, and non-Mexican-American Latino women. RESEARCH DESIGN AND METHODS -Homeostasis model assessments (HOMAs)of insulin sensitivity (HOMA%S) and ␤-cell function (HOMA%␤) were used. Stepwise multivariable ethnic-specific ANCOVA models were used to compare HOMA%S and HOMA%␤ between non-Hispanic whites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
103
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 44 publications
7
103
1
1
Order By: Relevance
“…Previous multiethnic cohort studies have reported the ethnic differences in insulin sensitivity and b-cell function (30). In the present study, the BMI of the subjects was relatively low in comparison with those in above studies, which may contribute to insignificant correlation between osteocalcin and HOMA-IR.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous multiethnic cohort studies have reported the ethnic differences in insulin sensitivity and b-cell function (30). In the present study, the BMI of the subjects was relatively low in comparison with those in above studies, which may contribute to insignificant correlation between osteocalcin and HOMA-IR.…”
Section: Discussioncontrasting
confidence: 48%
“…In particular, Asians are at risk for type 2 diabetes at a lower level of obesity, partly due to their increased predisposition to visceral adiposity (29) and reduced pancreatic ␤-cell function (30). In the metaanalyses, TCF7L2 rs7903146 showed the strongest effect (OR 1.44) in both Europeans and Asians.…”
Section: Discussionmentioning
confidence: 92%
“…However, an association between G6PC2 SNPs and type 2 diabetes was not observed in Europids. It is unclear whether ethnic differences in beta cell function, such as those suggested between Asian populations and populations of European descent in several studies [22,23], played a role in the effect of G6PC2 variants.…”
Section: Discussionmentioning
confidence: 99%